I and we: Hannah Arendt, participatory plurality, and the literary scaffolding of collective intentionality - Morgan, B; Rokotnitz, N; Budelmann, F; Zahavi, D (Pennsylvania State University Press, 2023)
This article examines Hannah Arendt’s contribution to notions of the “We” and tests key Arendtian concepts through relation and juxtaposition with philosophical and literary texts from different periods, thereby complicating discussions of (1) how individuals participate in, shape, and are shaped by various forms of “We”; (2) how, within collective participation, individuals come to care about being themselves; and (3) to what extent literary texts enable and encourage processes of identity construction and (re)configuration. For Arendt, the “place in the world which makes opinions significant and actions effective” (2017, 387–88) is “the result of our common labor, the outcome of the human artifice” (2017, 393)—the shared practices and institutions that Wittgenstein calls “forms of life” (2009, 15). In this article, the authors argue that by exploring and critiquing “forms of life” literature can expand the range of activities we recognize as fostering “participatory sense-making” (De Jaegher and Di Paolo 2007, 465). The three literary provocations presented here—Callimachus’s “Hymn to Apollo,” Thomas Mann’s The Magic Mountain, and Margaret Atwood’s Alias Grace—all interrogate the situated interactions of “I’s” and “We’s” that instantiate the “participatory plurality” of the shared world.